Policy Brief on Cybercrime Legal Framework in Malaysia - Shereen KHAN; Nasreen KHAN; Olivia TAN; Rossanne Gale VERGARA (Communications of International Proceedings, 2022)
Malaysia recorded an 82.5% increase in cybercrime in 2021 as cybercriminals are capitalising on the rise in new technologies and remote working platforms as a result of global pandemic outbreak. Interpol ranks Malaysia among the top three countries in terms of mobile banking malware detections and the increase in cyberthreat landscape shows that there is significant cybercrime vulnerabilities in Malaysia. Computer-related crimes offences are normally charged under the Penal Code which is the main statute in dealing with all the criminal offences and procedures even though Penal Code was not enacted to address cybercrimes. In fact, there is no specific existing legislation on electronic or computer-related identity theft or identity fraud. This policy brief presents the effectiveness of current cybercrime legislation in combating cybercrime in Malaysia and identifies promising good practices stemming from studies of cyberlaw legislation in other jurisdictions. The policy brief presents raising public awareness as one of the promising practices and calls on an urgent need to amend the legislation relating to cybercrime in Malaysia.
Keywords: cybercrime; cybersecurity; policy brief; cybercrime legislation